Soft Tissue Augmentation Principles and Practice - Galadari, Hassan (Springer Berlin Heidelberg, 2018)
The field of soft tissue augmentation has expanded rapidly in recent years. This book is distinguished from other works on the subject in that it is specifically designed as an easy-to-use practical guide. After essential introductory discussion of clinical anatomy and danger zones, information is presented on the various available dermal fillers and injection techniques. The use of dermal fillers for facial aesthetics and procedures in other parts of the body is then considered in detail. Reflecting the paradigm shift that has been occurring in the field, the most advanced techniques are highlighted. In addition, potential complications are thoroughly but succinctly discussed. The text is supplemented by informative color diagrams and images. Soft Tissue Augmentation: Principles and Practice will be of value for both novice and experienced practitioners.